Cognitive Dysfunction, Psychophysiological Regulation, and Psychosocial Factors in Psychosomatic Disorders: A Narrative Review - Dela Riadi (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2026)
Background: Psychosomatic disorders result from complex interactions among biological, psychological, cognitive, and social factors. Growing evidence suggests that cognitive dysfunction, particularly in attention, executive functioning, and working memory, contributes to the development and persistence of psychosomatic symptoms. This review aimed to synthesize current evidence on cognitive dysfunction, psychophysiological regulation, self-regulation mechanisms, and psychosocial factors associated with psychosomatic disorders..Method: A narrative review was conducted using articles published between 2016 and 2026 and retrieved from Scopus, PubMed, ScienceDirect, and ProQuest through a literature search conducted on April 24, 2026. The search strategy was based on the PICOS framework and included terms related to psychosomatic disorders, somatic symptom disorder, executive functions, attention, working memory, self-regulation, and psychosocial factors. Following the screening and eligibility assessment, 14 articles were included in the review.Result: The findings indicate that impairments in attention, executive functioning, and working memory are consistently associated with psychosomatic disorders and may influence symptom severity and treatment response. Psychophysiological regulation, particularly autonomic nervous system functioning, plays an important role in self-regulation and symptom management. Furthermore, psychosocial factors, including depression, illness beliefs, maladaptive coping, chronic pain, and childhood trauma, contribute to psychosomatic vulnerability and disease progression. Psychosomatic disorders are influenced by interactions among cognitive, psychophysiological, and psychosocial factors, highlighting the importance of integrated, patient-centered approaches to assessment and treatment.